Proses Berpikir Analogi Mahasiswa dengan Gaya Belajar Field Dependence dan Gaya Belajar Field Independence dalam Memecahkan Masalah Matematika - Lalu Sucipto (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
The purpose of this study was to measure the level of integral mastery in students in terms of the analogy thinking process of students with field dependence learning styles and field independence learning styles. Type of descriptive qualitative research in the form of field survey. To measure the cognitive style of the independent field students and field dependent instruments used by Witkin (1971) called the Group Embedded Figure Test (GEFT). The results showed that students with independent field learning styles had a higher level of integral mastery than students with field dependent learning styles.